Pola Komunikasi Orang Tua Terhadap Anak Autis DI Kelurahan Oebufu - Yuvine Marlene Cicilia Noach; Glorya Maharani Clarhend Noach; Frederiksen Victoranto Amseke (Ra'ah: Journal of Pastoral Counseling, 2021)
Humans cannot be separated from communication. Communication is a means/tool for humans to be able to interact socially. However, some people sometimes have difficulty communicating with different factors, such as autistic children, who are different from other children. This study aimed to find out how the communication patterns carried out by parents towards autistic children in Kupang. The method used in this research is descriptive qualitative research. The characteristics of the subjects in this study were a family with moderate autistic children—data collection techniques employing interviews as the primary method and observation as a supporting method. The results showed that this family used interactional communication patterns. The pattern of communication carried out by parents to autistic children will affect the parenting pattern carried out in a family. This family uses a democratic pattern. In addition, another supporting communication factor used by the parents is by using visual and audio media. Otherwise, the obstacle factor faced by the parents in communication with the autistic children is the lack of children’s focus since they have autistic disorders and children’s behaviour tends to hurt themselves.